Análise prospectiva de potenciais impactos socioeconômicos do Projeto de Integraç\~ao do Rio S\~ao Francisco com bacias hidrográficas do Nordeste Setentrional sobre a regi\~ao beneficiada - César Nunes de Castro; Monise Terra Cerezini (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– A significant portion of the northeastern territory of Brazil has a population and water resources such that, when combined, they result in low to very low water availability per inhabitant. Over time, numerous human interventions were carried out in the region in an attempt to mitigate the effects of the climate and the low natural water availability of the region on the life of the local population. Among these, perhaps the most ambitious, the transposition of the S\~ao Francisco, began to be built (channels, tunnels, water mains...) in 2007 and is in the final phase of implementation. This work aims to evaluate the possible socioeconomic impacts of the S\~ao Francisco transposition on the benefited region. Among the potential impacts, it is considered that in the medium term (until 2041) the basal flows transposed by the PISF to the East (10 m3 /s) and North (16.4 m3 /s) axes will probably be enough to meet the part of the deficit of demand for priority uses projected for the East axis and just over 90% of the deficit projected for these uses in the North axis in 2041. To increase the water security of the dispersed rural population, complementary measures to the PISF will have to be adopted, such as, for example, the continuous investment in cisterns and periodic actions, necessary in periods of occurrence of extreme weather phenomena, such as that of water distribution through water trucks.
10419/284862
Keywords: Q25; Q28; 330; Brazil's Northeast; S\~ao Francisco River water transposition; social and economic impacts